Load Balancing and its Algorithms in Cloud Computing: A Survey - Sajjan, RS; Yashwantrao, Biradar Rekha (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides on-demand access to distributed resources on paid basis. Everybody wants to use these services to reduce the cost of infrastructure and maintenance, therefore the load on cloud is increasing day by day. Balancing the load is one of the most important issue that cloud computing is facing today. The load should be distributed fairly among all the nodes. Proper load balancing can reduce the energy consumption and carbon emission. This will helps to achieve Green Computing. There are many algorithms for load balancing. All these algorithms work in different ways and have some advantages and limitations. The most important for load balancing algorithms is to consider the characteristics like fairness, throughput, fault tolerance, overhead, performance, and response time and resource utilization. This paper mainly focuses on the concept of load balancing, literature survey on load balancing techniques and different measurement parameters.